Space traffic control - Eves, Stuart (Progress in astronautics and aeronautics ;, 2017)
In Space Traffic Control, Stuart Eves makes a deliberate analogy between operations in space and air traffic control. Space Traffic Control considers the systems and procedures which can provide solutions to the problem of space debris and concludes with recommended approaches.